Struktur Komunitas Artropoda pada Ekosistem Padi Tanpa Perlakuan Pestisida - Eddy Mahrub (Universitas Gadjah Mada, 1998)
Generally, rice ecosystem was les stable because the structure of natural community often change, and it may cause decrease in the natural biodiversity. The research has been done in the lowland ricefield during wet and dry season without pesticides application. Observation was started when the plant (IR64) was 7 days old after transplanting with interval of 8 days until one week before harvest, to collect the arthropods from each samples. The objectives were to study the structure of community of arthropods during wet and dry season and to study food web chain in natural ecosystem and its implementation in the Integrated Pest Management Program. The results showed that in rice ecosystem four arthropod groups or guilds, was found i.e. Pests, Predators, Parasites and Neutral Arthropods. The diversity and species abundance of arthropods were high but the highest abundance of arthropods was found on the member of certain order and family only. The population of pest was lower than predator. The relative abundance of pests were 5.75% in wet season and 8.57% in dry season, while predators were 27.96% in wet season and 33.88% in dry season. The population density of spider predators especially Lycosa sp. during wet and dry season were very high. It was supported by the abundant of neutral arthropods as alternate prey when the pest population was very low. This condition may support negative feed back interaction and increase the potential of natural control in the absence of pesticide application.